Application of Coliphage Lysate: A Preliminary Trial to Treat an Experimental Escherichia coli Infection in Broiler Chicken - Sajjad, M.; Rahman, S.U.; Hussain, I.; Rasool, M.H. (International Journal of Poultry Science, 2004)
Pathogenic E. coli was isolated from the birds suffering from colibacillosis showing characteristic lesions. Two types of coliphages T1 and T4 were isolated from the sewage water collected from different areas of Faisalabad, Pakistan. These phages were separately tested for in vitro lysis of their host cell on tryptone agar plates, with equal (1:1)) concentration (107 CFU and 107 PFU) of E. coli and phages, which resulted in complete absence of colonies of bacteria after 10 minutes. When phage concentration was reduced (1:½ and 1::¼), colonies continued to appear even after 10 minutes. Later these phages were mixed and evaluated through in vivo trials in broiler chickens of two weeks age. A total of 100 broilers were divided into four groups (A, B, C and D) having 25 birds in each group. First three groups were administered with equal (1:1) concentration of phages as well as E. coli (107/ml) through oral, intraperitoneal and intramuscular routes. The control group (D) was further subdivided into two groups of D1 and D2, both of which were deprived of phages and E. coli respectively. The 13 birds of group D2 that were given only the phages did show neither the signs of disease nor mortality. The results indicated a good protection level using coliphages when compared with the control group. It was concluded that phages may be used effectively as good alternatives of those antibiotics to which bacteria have become resistant.